A prospective clinical trial to compare the performance of dried blood spots prenatal screening for Down's syndrome with conventional non-invasive testing technology. Issue 5 (March 2017) - Hu, Huiying; Jiang, Yulin; Zhang, Minghui; Liu, Shanying; Hao, Na; Zhou, Jing; Liu, Juntao; Zhang, Xiaojin; Ma, Liangkun
To evaluate, side by side, the efficiency of dried blood spots (DBSs) against serum screening for Down's syndrome, and then, to construct a two-tier strategy by topping up the fetal cell-free DNA (cfDNA) secondary screening over the high-risk women marked by the primary blood testing to build a practical screening tactic to identify fetal Down's syndrome. One thousand eight hundred and thirty-seven low-risk Chinese women, with singleton pregnancy, were enrolled for the study. Alpha-fetoprotein and free beta human chorionic gonadotropin were measured for the serum as well as for the parallel DBS samples. Partial high-risk pregnant women identified by primary blood testing (n = 38) were also subject to the secondary cfDNA screening. Diagnostic amniocentesis was utilized to confirm the screening results. The true positive rate for Down's syndrome detection was 100% for both blood screening methods; however, the false-positive rate was 3.0% for DBS and 4.0% for serum screening, respectively. DBS correlated well with serum screening on Down's syndrome detection. Three out of 38 primary high-risk women displayed chromosomal abnormalities by cfDNA analysis, which were confirmed by amniocentesis. Either the true detection rate or the false-positive rate for Down's syndrome between DBS and the serum test is comparable. In addition, blood primary screening aligned with secondary cfDNA analysis, a "before and after" two-tier screening strategy, can massively decrease the false-positive rate, which, then, dramatically reduces the demand for invasive diagnostic operation. Impact statement: Children born with Down's syndrome display a wide range of mental and physical disability. Currently, there is no effective treatment to ease the burden and anxiety of the Down's syndrome family and the surrounding society. This study is to evaluate the efficiency of dried blood spots against serum screening for Down's syndrome and to construct a two-tier strategy by topping up the fetal cell-free DNA (cfDNA) secondary screening over the high-risk women marked by the primary blood testing to build a practical screening tactic to identify fetal Down's syndrome. Results demonstrate that fetal cfDNA can significantly reduce false-positive rate close to none while distinguishing all true positives. Thus, we recommend that fetal cfDNA analysis to be utilized as a secondary screening tool atop of the primary blood protein screening to further minimize the capacity of undesirable invasive diagnostic operations.